Cultural dialogue in the Islamic perspective and its role in achieving coexistence among civilizations - Al-Shammari, Shaymaa Nasser Hussain (Journal of Humanities & Social Sciences, 2023)
This study aims to shed light on the role and importance of cultural dialogue from an Islamic perspective in achieving ways of coexistence among civilizations. The results are: 1. The concept of dialogue is one of the implications referred to by the Holy Qur’an in making it a refined method of communication between civilizations and the cross-fertilization of ideas, but within methodological controls that achieve the goal of cultural dialogue through its value and impact.2. Spreading cultural dialogue between civilizations and learning all related etiquette and controls, aims to make all civilizations adopt a sound behavior to care for members of society in their lives and improve their conditions.Cultural dialogue has positive scientific and cognitive effects on individuals, societies, nations and all civilizations, including: achieving the principle of peaceful coexistence among civilizations, contributing to the development of the field of intellectual and knowledge production, enhancing the preservation of the identity of nations and civilizations by preserving the ancient history of all civilizations.
Keywords: dialogue; culture; cultural dialogue; civilization; dialogue in the Qur’an; dialogue in the Sunnah of the Prophet